PROBLEMS OF CONSTRUCTING WIND-DIESEL POWER PLANTS IN HARSH CLIMATIC CONDITIONS - Vasilievich Elistratov, Victor; Knežević, Miloš; M.A, Konishchev; Konishchev, Michael (Journal of Applied Engineering Science, 2014)
The energy supply of buildings on the basis of renewable energy is a topical problem of the modern construction science. Wind power is the most modern and perspective direction in renewable energy both in Russia and Serbia. In the northern regions of Russia, the increase of reliability and efficiency of power supply is suggested to be solved by constructing wind-diesel power plants and optimizing the composition of equipment, parameters and modes of operation. In the article, the major problems faced during the process designing of wind-diesel power plants in harsh climatic conditions are considered. The complexity is associated with building and using wind turbines. There are the problems of transport logistics, of the construction on the permafrost, the installation and adaptation of equipment to harsh climatic conditions. In the article, the major issues increasing the reliability of operation are described. A number of considered issues are analyzed and solutions are proposed regarding the design documentation to construction of WDPP in the Yamal-Nenets Autonomous District. The recommendations for choosing the basic equipment are described. The parameters of WDPP with high penetration are optimized using the software package HOMER 2.81.
Keywords: Harsh climatic conditions; Building; Wind turbine; Wind-diesel power plant; Energy-efficient technologies in building